(untitled) (Journal of the College of Education for Women, 2019)
The study of morphometric tectonic characteristics of Trifaoui Valley Basin and knowledge of tectonic activity in the study area to be a useful tool to identify and measure the tectonic activity. Some indicators have been used for the river basin in order to learn pelvic tilt and symmetry factor asymmetry and cross terrain of the valley was a definitive classification of indicators geomorphological and show off Index (AF) to the pelvis tilted towards the north and this Match with the direction of the public trough. The index (T) Non-displacement of the mainstream of the basin of river from the center of the basin, and the index (SL) to the tectonic activity index (VF) Basin Trifaoui neutral in terms of lifting the tectonic processes of weathering and erosion process, making the floor of the valley take consistent values between the two operations, which gave valuable insight for the activity and tectonic evolution of the study area